Terror on the Maine frontier : The ordeal and triumph of John Gyles - Gawalt, Grard W. ([Place of publication not identified] : [the author], 2023)
Terror on the Maine Frontier relates the hardships of life in early colonial Maine, told through the diary of John Gyles, who was captured and held enslaved for nine years.
Includes index.
Includes brief references to Castine.
Includes bibliographical references (pages 153-157).
Keywords: Captivity narratives -- America; Diaries; Maine -- History